Evaluating the Impact of Community Experience on Purchase Intention in Online Knowledge Community - Zhao, Hong; Shi, Qiaohong (Frontiers in Psychology, 2022)
Community experience has an important influence on the brand building of an online knowledge community. By enhancing the community experience of members, it can promote the building of an online knowledge community and increase users' purchase intention. Although existing research has explored the influence model of community experience, there is a dearth of research regarding the influence of community experience on purchase intention. To this end, this study uses the online knowledge community experience as a theoretical basis to construct a mediating model to examine the behavioral patterns of consumers using the online knowledge communities and to explore in detail the mechanisms of the different dimensions of the community experience on purchase intention. It was found that not only the three dimensions of community experience (i.e., information experience, entertainment experience, and interactive experience) had a significant effect on brand identity, but also brand identity had a significant effect on purchase intention. The study also confirmed that brand identity mediates the relationship between community experience and purchase intention. This study reveals the mediating mechanism of community experience on purchase intention and helps to effectively guide the innovative management practices of the online knowledge community.